Hubungan Kampanye Politik Mas-Dipa dengan Pengetahuan Politik Pemilih Pemula Desa Rendang dalam Pilkada Karangasem 2015 - Yuni Uttari, Ni Luh Putu; Amanda Gelgel, Ni Made Ras; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2017)
One of the significant changes in the Pilkada Serentak 2015 is the efficiency of political campaign activities. This may affect the role of political actors in giving political knowledge to voters, especially young voters. This study aims to see how the relationship of political campaigns with political knowledge seen through political campaigns conducted by Mas-Dipa in Pilkada Karangasem 2015. This study uses a quantitative approach with correlation analysis. Primary data source of this research is questionnaire distributed to young voters in Desa Rendang and the secondary source of this research is obtained through Kantor Kepala Desa Rendang. The result shows that Mas-Dipa’s political campaign has significant, strong and unidirectional relationship. The intensity of voter participation in the village of Rendang in the political campaign of Mas-Dipa is quite frequent and the level of political knowledge is good. Keyword: Political Campaign, Political Communication, Political Knowledge, Young                      Voters.